Access Denied: Sex workers’ exclusion from COVID-19 relief in the United States - Grant, Mariah (Anti-Trafficking Review, 2023)
This short article provides an overview of the US government’s response to COVID-19 and the exclusion of sex workers from pandemic relief. It details the impacts of this exclusion, including how sex workers and advocates were forced to prioritise emergency service provision over longer-term policy goals. The article concludes that the exclusion of sex workers from COVID-19 relief is part of the US government’s broader history of discriminating against people involved in the sex trades and hindering advancements in policies to protect sex workers’ human rights.